As festas da cidade de Porto Nacional - TO: um olhar dos ativistas culturais - Feitosa, Thalyta de Cássia da Silva (Universidade Federal do Tocantins, 2017)
The city of Porto Nacional is located in the interior of the state of Tocantins and is known for its historical and cultural importance. During the development of this research, it was possible to observe that in it several types of partyes, and its celebrations are quite diverse, being, therefore, celebrations, of religious character, to civic and profane celebrations. However, we highlight in this work those that happen today and that are considered important in the cultural scope, from the opinion of the cultural activists of the city. In this sense, the main objective of this work was to investigate how the celebrations that take place in the city of Porto Nacional, and that are considered by the cultural activists important in the cultural scope, contribute to the strengthening of the local culture. The research is inserted in the perspective of the renewed cultural geography and had as main concepts approached culture and the place, since they are interconnected to our object of study: party. Regarding the methodology, the research was carried out through the qualitative approach and had as main techniques the bibliographical and field research. A total of 13 cultural activists were interviewed between October and November 2016, in order to identify the parties considered by them as a cultural reference for the city of Porto Nacional. For analysis and description of the parties, the main sources used were bibliographical and oral. Regarding the oral source, we have seen that about some festivals cited by cultural activists there was no information written in books or articles. Therefore, it was necessary to interview people responsible for the organization and collaborators (people who attend or who were part of the party organization) between March and May 2017. Some of these interviews took place via electronic media (Facebook and Whatsapp) and others in person. At the end of the research, we consider that, in spite of the changes that the partyes are going through (because the culture is dynamic), as they happen, and only because they are realized, they contribute to the strengthening of the local culture, because it is a way for individuals to experience what is part of their culture.